The Architecture of American Slavery: Teaching the Black Lives Matter Movement to Architects - Zipf, Catherine (Radical Teacher, 2016)
The spatial dynamics surrounding the murder of Trayvon Martin are rarely discussed in architecture schools. Yet, the racial biases in our landscape are key to the agenda of the Black Lives Matter movement. This article tells the story of how these issues found their way into a course on the architecture of American slavery.  As the semester progressed, students discovered how the remnants of slave spaces, along with the racial biases they embodied, have contributed to the rise of the Black Lives Matter movement.